Review on Seismic Behavior of L-Shaped Multistorey Buildings with Varying Bay Lengths: A Literature Perspective - Roshan Kumar Sahu; Dr. Tarun Kumar Rajak (International Journal of Scientific Research in Civil Engineering, 2025)
Two examples of G+10 storey L-shaped buildings are examined in this paper. Engineers can create structures that meet performance standards and utilize resources efficiently by taking into account the unique imperfections. We examined the same building with different bay lengths to differentiate the other three designs from the original model. The bay length of the basic model is 27 meters, that of the second model is approximately 33 meters, that of the third structure is 39 meters, and that of the fourth model is 45 meters. STAAD.Pro will be used in this study to assess and develop a model of an irregularly shaped building. To demonstrate the benefits of using STAAD.Pro for irregular building design, a number of metrics, including shear force, bending moment, storey drift, etc., will be utilized to compare the findings with simplified analytical methods. In this paper we are conducting an audit of literatures regarding irregular building desing.
Keywords: irregular L-shaped buildings; storey drift; bending moment; shear force; earthquake analysis; STAAD.Pro